Review of Dermoscopy and Reflectance Confocal Microscopy Features of the Mucosal Melanoma - Andrea De Pascalis (Diagnostics, 2021)
Mucosal melanoma is a rare tumor with aggressive biological behavior and poor prognosis. Diagnosis is often performed at an advanced stage when the lesions become symptomatic. Although dermoscopy and reflectance confocal microscopy (RCM) are widely used techniques for the diagnosis of cutaneous tumors, their use for mucosal lesions is not well established, probably because the latter are rarer. The objective of this study was to evaluate current literature on these imaging techniques for mucosal melanoma. We searched in PubMed and Cochrane databases all studies up to October 2020 dealing with dermoscopy, RCM, and mucosal melanoma. We found that the most relevant dermoscopic features were structureless pattern and/or the presence of multiple colors. RCM examination mainly showed numerous basal hyper-reflective dendritic cells and loss of normal architecture of the papillae of the lamina propria. Although diagnostic algorithms have been proposed for both techniques, the limit of these methods is the absence of large studies and of standardized and shared diagnostic criteria.